Dapagliflozin Presented Nonalcoholic Fatty Liver Through Metabolite Extraction and AMPK/NLRP3 Signaling Pathway - Lin, Deng; Song, Yuling (Hormone and Metabolic Research, 2022)
In recent years, the incidence rate of nonalcoholic fatty liver disease (NAFLD) has been increasing year by year. The experiments conducted on rat elucidated the effect and underlying mechanism of dapagliflozin in NAFLD. Sprague Dawley rats were fed with HFD (Fat accounts for 52%, carbohydrate 34% and protein 14%) for 12 weeks as NAFLD model. Dapagliflozin presented NAFLD in rat model. Dapagliflozin reduced oxidative stress and inflammation in rat model of NAFLD. Dapagliflozin reduced oxidative stress and inflammation in vitro model of NAFLD. Dapagliflozin in a model of NAFLD metabolized into histamine H1 receptor, caffeine metabolism, mannose type O-glycan biosynthesis, choline metabolism in cancer, tryptophan metabolism, and glycerophospholipid metabolism. Dapagliflozin induced AMPK/NLRP3 signaling pathway. The regulation of AMPK/NLRP3 signaling pathway affected the effects of dapagliflozin on nonalcoholic fatty liver. In summary, dapagliflozin plays a preventative role in NAFLD through metabolite extraction, the inhibition of oxidative stress, and inflammation by AMPK/NLRP3 signaling pathway. Dapagliflozin may be a potential therapeutic agent for oxidative stress and inflammation in model of NAFLD.
Keywords: dapagliflozin; nonalcoholic fatty liver; metabolite extraction; AMPK; NLRP3